Analytical method Development and Validation for the estimation of Pioglitazone hydrochloride in Bulk and Tablet dosage form by UV_Spectroscopy - M.Venkatesh; B.Narender; D.Anusha; G.Srikanthbabu; J.Mounika; S.Laxman (IJPAR JOURNAL, 2013)
This paper describes the analytical method suitable for validation of Pioglitazone hydrochloride by UV Spectrophotometric method. The method utilized UV spectroscopy and the solvent system was consists of 6 N Glacial acetic acid at wave length 270 nm. Validation experiments were performed to demonstrate Specificity, Precision, Linearity, Accuracy, ruggedness. The method was linear over the concentration range of 10-50 µg/ml. The Proposed method was simple, sensitive & reliable with good Precise, Accurate, and Reproducible and rapid for the determination of Pioglitazone. The commercial formulations are estimated without interference. Hence this method can be used for routine determination of Pioglitazone hydrochloride in bulk and their pharmaceutical dosage forms.